Pre-pregnancy complications - associated factors and wellbeing in early pregnancy: a Swedish cohort study - Gudnadottir, Unnur; Du, Juan; Hugerth, Luisa W.; Engstrand, Lars; Schuppe-Koistinen, Ina; Wiberg Itzel, Eva; Fransson, Emma; Brusselaers, Nele (BMC pregnancy and childbirth, 2023)
Background Many couples experience difficulties to become pregnant or carry a pregnancy to term due to unknown causes. Here we define pre-pregnancy complications as having prior recurrent pregnancy loss, prior late miscarriages, time to pregnancy more than one year, or the use of artificial reproductive technologies. We aim to identify factors associated with pre-pregnancy complications and poor well-being in early pregnancy. Methods Online questionnaire data from 5330 unique pregnancies in Sweden were collected from November 2017 – February 2021. Multivariable logistic regression modelling was used to investigate potential risk factors for pre-pregnancy complications and differences in early pregnancy symptoms. Results Pre-pregnancy complications were identified in 1142 participants (21%). Risk factors included diagnosed endometriosis, thyroid medication, opioids and other strong pain medication, body mass index > 25 kg/m 2 and age over 35 years. Different subgroups of pre-pregnancy complications had unique risk factors. The groups also experienced different pregnancy symptoms in early pregnancy, where women that had experienced recurrent pregnancy loss were at higher risk of depression in their current pregnancy. Conclusion We report one of the largest pregnancy cohorts with high frequency of pre-pregnancy complications compared to the Swedish population. Prescribed drug use and body weight were the top potentially modifiable risk factors in all groups. Participants that experienced pre-pregnancy complications also had higher risk of depression and pregnancy problems in early pregnancy.